Perwujudan Nilai Budaya Timur dalam Penghidupan Kembali Pasal Penghinaan Presiden dan Wakil Presiden - Deny Noer Wahid; Ilham Dwi Rafiqi (Fakultas Hukum Universitas Hang Tuah, 2022)
The draft criminal code (RKUHP) has again received a sandstone in its ratification. This is due to several articles that are judged by some people. One of them is about the re-entry of the Article of contempt for the head of state which again reaped polemics in the community. So that with the re-regulation of the article, it is feared by many circles to be a form of defiance of the constitution and violations of free speech which eventually enter into violations of human rights. With the emergence of the article, there has been a lot of polarization in the community between those who support the existence of the article and the contras to the article. To discuss this, normative legal research methods with a conceptual approach, a statutory approach and a historical approach are used. The results of the study show that the reappointment of the article of contempt for the head of the nation's values is not contradictory because the article falls into the category of rechtdelicten. This contempt clause is present because the President and Vice President are icons of the country that can have an impact on the potential for division of society and also harm to other countries.